THE INCOME ANALYSIS OF UNIT PEMBENIHAN RAKYAT (UPR) IN TANJUNG HARAPAN SUB-DISTRICT SOLOK CITY,WEST SUMATRA PROVINCE - Ulfa Wahyuni; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study aims to analyze the income of UPR,and analyze the feasibility of the Unit Pembenihan Rakyat (UPR)whether it is appropriate to proceed or not. This research was conducted in May 2018 at UPR which is located in Tanjung Harapan Subdistrict, Solok City, West Sumatra Province.The research method uses survey methods.Respondents were taken in this study is 4 people including the manager / owner of each UPR in Sub Tanjung Harapan Solok.The results of this study indicate a total investment of IDR. 794.542.000  The highest total investment amount is IDR. 219.283.000 while the smallest total investment is IDR. 173.797.000. The average total production cost is IDR. 112.628.151 the largest total production cost is Rp. 140.524.500 and the smallest is IDR. 90.012.675.The average income is IDR. 5.003.903. The highest income is UPR Tanjung Paku Jaya, the lowest income is UPR Bina Mandiri Sejahtera with an income of IDR. 3.715.718 However, for UPR Tanjung Paku Jaya, which conducts minapadi activities is IDR. 7.247.958. The feasibility analysis of Revenue Cost of Ratio (RCR) for each UPR actor in Tanjung Harapan Subdistrict, Solok City, the largest is  1,6 and the smallest is 1,4. The average payback period of capital (PPC) of fish hatchery business conducted by the UPR perpetrator is 3,5 for the highest period of capital (PPC), which is 4,9 and the lowest is 1,9.Keywords: Unit Pembenihan Rakyat (UPR) , Income, Business Feasibility